The Effect of Flooding Technique Training on Anxiety in Arguing Students - Zarnalia Amanda; Roudha, Ananda Alya; Rizqiyah Nabila Auliati (CV. Era Digital Nusantara, 2024)
The study aims to explore the influence of engineering training flooding against the level of anxiety in a student's argument. Experimental methods are used to involve students from the islamic political study program at the islamic university of raden's fatah palembang. The technique of flooding, which involves the use of imaginative techniques, has proved to be effective in overcoming fear and anxiety in cases such as phobias, obsessive, and psychotics. In this study, the technique of flooding is used to help students overcome anxiety in argument. Research indicates a significant difference between the anxiety levels before and after the training of the technique flooding, showing the effectiveness of this technique in reducing anxiety. It is hoped that this study will provide a useful recommendation for improving the effectiveness of training techniques flooding into anxiety in student argument.